2016
DOI: 10.9775/kvfd.2016.15001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Borax on Inflammation, Haematological Parameters and Total Oxidant-Antioxidant Status in Rats Applied 3–Methylcholanthrene

Abstract: In this study was investigated effects of borax (BX) on inflammation markers, haematolojical parameters and total oxidant (TOS)-antioxidant status (TAS) in rats applied 3-methylcholanthrene (3-MC). In this research a total of 24 Wistar Albino rats were used. They were divided into 4 groups each containing 6 rats. 1st group was separated as a control group. 3-MC was applied twice a week first 2 weeks 25 mg/kg dose to the 2nd group with i.p. way. BX was given to 3rd group 300mg/L/day dose with drinking water dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The findings of our study show that it improved brain inflammation, immunohistochemical parameters (iNOS and TNF-α) and blood tissue oxidative stress parameters (TAS, TOS), and protected rotenone-induced dopaminergic damage with the local and systemic increase in antioxidant capacity. Studies with boric acid also reported the oxidant capacity and other proinflammatory biomarkers decreased and total antioxidant capacity increased (13,(49)(50)(51).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The findings of our study show that it improved brain inflammation, immunohistochemical parameters (iNOS and TNF-α) and blood tissue oxidative stress parameters (TAS, TOS), and protected rotenone-induced dopaminergic damage with the local and systemic increase in antioxidant capacity. Studies with boric acid also reported the oxidant capacity and other proinflammatory biomarkers decreased and total antioxidant capacity increased (13,(49)(50)(51).…”
Section: Discussionmentioning
confidence: 96%
“…Boric acid is odorless, tasteless, and stable in the air. It is a weak acid in the form of white crystals, which is absorbed quite rapidly and excreted from the body in the urine (12,13). The World Health Organization (WHO) recommends that the average safe intake level of boron for adults should be 1-13 mg/day, and the upper limit should be 20 mg/day (14).…”
Section: Investigation Of the Pharmacological Behavioral And Biochemi...mentioning
confidence: 99%
“…Comba et al (32) reported elevated levels of TOS and OSI by 3-MC administration. The authors performed their study in blood sera of intraperitoneally 25 mg/kg 3-MC applied rats.…”
Section: Discussionmentioning
confidence: 98%
“…This mineral, which has serious reserves in our country, has widespread uses (glass, ceramics, cleaning, whitening, cosmetics, metallurgy, nuclear, computer, aircraft industry, energy industry, agriculture and health) (Helvacı, 2003). Borax mineral is effective on hormone and lipid metabolism as well as free radicals of many enzymes (Comba, Oto, Mis, Özdemir, & Comba 2016;Acaroz et al, 2019). One of the most common boron minerals, colemanite (COL), is a monoclinic crystalline calcium borate mineral with chemical formula 2CaO • 3B2O3 • 5H2O (Kızılca & Copur, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common boron minerals, colemanite (COL), is a monoclinic crystalline calcium borate mineral with chemical formula 2CaO • 3B2O3 • 5H2O (Kızılca & Copur, 2015). Boron minerals are effective in activity of many enzymes, as well as hormone and lipid metabolism (Comba et al, 2016). Although their action mechanisms are not clear, it has been demonstrated that borates are not metabolized and control the damage of the organism by altering the oxidative stress parameters (Pawa & Ali, 2006;Acar, İnanan, Zemheri, Kesbiç, & Yılmaz, 2018;Alak et al 2018;Alak et al, 2019a;2019b;2019c).…”
Section: Introductionmentioning
confidence: 99%